Flamenco music : history, forms, culture - Manuel, Peter, 1952- (University of Illinois Press, 2023)
"An iconic symbol of Spain, flamenco has become a global phenomenon. Peter Manuel offers English-language readers a rare portrait of the music's history, styles, and cultural impact. Beginning with flamenco's Moorish and Roma influences, Manuel follows the music's evolution through its consolidation in the mid-1800s and on to the vibrant contemporary scene. An investigation of flamenco's major song-types looks at rhythm and compás, guitar technique, and many other aspects of the music while Manuel's description and analysis of the repertoire range from soleares and bulerías to tangos. His overview of contemporary flamenco culture provides insight into issues that surround the music, including globalization, gender dynamics, notions of ownership, and the ongoing debates on purity versus innovation and the relative roles played by Gitanos and non-Gitanos. Multifaceted and entertaining, Flamenco Music is an in-depth study of the indelible art form that inspires enthusiasts and practitioners around the world"--